DIGITAL TRANSFORMATION AND THE CYBERSECURITY OF INFRASTRUCTURE SYSTEMS IN THE OIL AND GAS SECTOR - Badi, Sulafa (2020)
Digitisation has rapidly increased within the oil and gas industry. The sector is embracing tech nologies such as the “digital oilfield” and internet of things (IoT) solutions to increase the effi ciency of asset monitoring, the speed of problem identification and resolution, and effective decision-making (Rosner et al., 2017). Supervisory control and data acquisition (SCADA) systems, industrial control systems (ICS), and programmable logic controllers (PLCs) are also increasingly integrated into operational technology (OT) networks to automate physical processes through valves, pumps, motors, sensors, and controllers, allowing operational systems to be centrally accessed, measured, monitored, and controlled. With the twenty-first century called the golden age of digital transformation in the oil and gas sector, the increased connectivity of cyber-physical systems (CPSs) will generate new opportunities for organisations such as greater safety, reliability, and efficiency.